5-3(4m-5)=-16

Simple and best practice solution for 5-3(4m-5)=-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3(4m-5)=-16 equation:


Simplifying
5 + -3(4m + -5) = -16

Reorder the terms:
5 + -3(-5 + 4m) = -16
5 + (-5 * -3 + 4m * -3) = -16
5 + (15 + -12m) = -16

Combine like terms: 5 + 15 = 20
20 + -12m = -16

Solving
20 + -12m = -16

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + -12m = -16 + -20

Combine like terms: 20 + -20 = 0
0 + -12m = -16 + -20
-12m = -16 + -20

Combine like terms: -16 + -20 = -36
-12m = -36

Divide each side by '-12'.
m = 3

Simplifying
m = 3

See similar equations:

| b=9 | | 3/7x+4=-1/2 | | 9x-2+5x-61=7x | | 20x+24x= | | 3/7x+4=-1/4 | | 3.14d=6.24 | | 12x-9+1x+2=11 | | 9+-4x+x=66 | | 5=10x+25 | | 5x=10x+25 | | 11=-ax+4 | | 63x+49=12x+100 | | x+qx=r | | 3x/2=4x/5-7/5 | | (x+2)/(2x-6)=3/8 | | 51/2+63/4 | | 4/8=40/x+8 | | 8-2(2x+3)=-11+3(x+1) | | 6x+4a+10=3 | | 2x^2-6xy+5y^2=7 | | 4/8=x+8/40 | | 1/8=x/56 | | 28-14/7+4 | | 231/16-123/8 | | -6r+3-5+8+r-6= | | 231/16/123/8 | | 5/4x-3=7 | | x-4a+6=-5 | | 7x-4x-8+2x=42 | | 3x+13y=154 | | 4x+2-3x+5=3+x+4 | | -3(x+3)+4x=10 |

Equations solver categories